Steam Explosion Modified κ-Carrageenan Structure and Its Jelly Application - Mengfan Lin; Qingyu Yang; Changrong Wang; Zebin Guo (Gels)
Steam explosion (SE) technology enhances the extraction efficiency of bioactive compounds and their physicochemical properties. This study compared the structural characteristics of κ-carrageenan extracted by SE-assisted alkali treatment and conventional alkali treatment from Eucheuma, as well as the quality attributes of the resulting jellies. The results indicate that SE treatment did not alter the species of carrageenan, but it significantly elevated the content of characteristic carrageenan groups, with the sulfate group content and 3,6-anhydrogalactose (3,6-AG) content increasing by 15.86% and 45.08%, respectively. The jellies prepared with κ-carrageenan following SE treatment demonstrated a more stable gel network structure, with an 80.9% increase in gel strength at a 1.5% κ-carrageenan concentration; the water precipitation rate of these jellies was minimized to 7.96 ± 0.69% when κ-carrageenan was added at a 1.7% concentration. These results suggest that SE treatment provides useful information for the application of κ-carrageenan in jelly.